Practice education facilitators perceptions and experiences of their role in the clinical learning environment for nursing students: a qualitative study - Cathrine Mathisen; Ida T. Bjørk; Lena G. Heyn; Turid-Iren Jacobsen; Elisabeth H. Hansen (BMC Nursing, 2023)
Abstract Background Clinical placement is recognised as essential for nursing students’ development of clinical competence. However, difficulties in providing supportive clinical learning environments are a well-known challenge in nursing education. In Norway, the use of nurse educators in joint university and clinical roles has been recommended as an initiative to strengthen the clinical learning environment and enhance the educational quality. In this study we use the term practice education facilitator in a generic sense for these roles. The aim of this study was to explore how practice education facilitators can contribute to strengthen the clinical learning environments for nursing students. Methods This study has a qualitative explorative design with a purposive sample of practice education facilitators affiliated to three different universities located in southeast, mid-, and northern Norway. Individual in-depth interviews with 12 participants were conducted during spring 2021. Results A thematic analysis resulted in four themes: “coherence between theory and practice”; “student support and guidance during placement”; “supporting the supervisors to support the students” and “factors influencing the practice education facilitators’ performance in their role”. The participants experienced that the practice education facilitator role contributed to strengthened clinical learning environments. However, their performance in the role was found to be contingent upon factors such as time allocated for the role, personal and professional attributes of the post holder, and a common understanding within the organisations regarding practice learning and role remits for the practice education facilitator. Conclusions Findings indicate that the practice education facilitator role can be a valuable resource for clinical supervisors and nursing students in clinical placement. Moreover, nurse educators who are familiar with the clinical area, and who are insiders in both settings, are ideally placed to contribute to ...